Sufism and Pesantren as the Part of Our Islamic and Indonesian Identity - Baeedhowi Baedhowi (The Institute of Research and Service Community IPMAFA Pati, 2021)
Tasawuf or Sufism in pesantren is an important material teaching that Muslims in Indonesia are very familiar. Historically, this social reality is important to understand that the beginning of Islamization here has put forward the nuances of Sufism. Saints and ulama such as Walisongo in Java are teachers of Islamic religion who have a very Sufistic nuance in their teachings. They attach great importance to this esoteric aspect of religion. The characteristic of Sufism that they spread is Ghazalian centric and accommodate social smoothness. In this way, the characteristic of their Sufism can still be integrated with the existing local cultures, so that their wisdom and religiosity can provide peace and enlightenment as well as harmony with the social realities and locality. This article wants to introduce the characteristic of Sufism and the role of pesantren as exemplified by the saints (Walis) in Java as an